APHALLIA: A VERY RARE CONGENITAL ANOMALY, WITH ASSOCIATED GENITOURINARY AND ANO-RECTAL MALFORMATION - Nisar, Muhammad Umar; Akhtar, Nadeem; Gondal, Mudassar Fiaz; Sikander, Samer; Viqar, Sana (Journal of Ayub Medical College Abbottabad, 2018)
Aphallia or penile agenesis is very rare congenital anomaly of unknown cause occurring 1 in 30 million live births. Very little has been written in literature about aphallia. There is absent phallus and urethra may open abnormally in perineum or into rectum posing various surgical, social and psychological implications as the child grows. We are presenting 03 cases of aphallia with associated congenital anomalies such as unilateral renal agenesis, bilateral undescended testes, anorectal malformation and rectovasical fistula. Keywords: Aphallia; Penile agenesis; Absent penis; Ambiguous genetalia; Phalloplasty; Neo-phallus; Penile reconstruction